Power usage effectiveness metrics to measure efficiency and performance of data centers - Uddin, Mueen; Alsaqour, Raed A.; Shah, Asadullah; Saba, Tanzila (Natural Sciences Publishing Corporation, 2014)
Intensifying computational demand from enterprises has driven the growth of large, multifaceted data centers to manage current Internet, financial, commercial, and business applications. A data center comprises thousands of servers and other equipment that require substantial amounts of power to operate. This condition results in numerous challenges for the data centers industry, such as massive energy consumption, under utilization of installed equipment, emission of greenhouse gases, and effect on global warming. This paper highlights the significance of identifying metrics to determine the performance and efficiency of a data center, which can help su ch a facility achieve operational cost savings through proper implementation of performance-measuring metrics. This paper discusses the implementation of power usage Effective metrics in a tier-level center in Pakistan. The results show that the overall performance value of the facility is 3.3, which indicates poor and inefficient operations.